DISFUNGSI WEF DALAM GLOBAL GENDER GAP INDEX REPORT TERHADAP PELAKSANAAN KESETARAAN GENDER DI AFGHANISTAN TAHUN 2021 – 2023 - Putri, Tessa Alfiani; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
In 2021-2023, WEF declared Afghanistan as the country with the worst gender equality with an index that always decreases from year to year in the Global Gender Gap Index Report. Afghanistan is the country that always ranks at the bottom of the overall gender equality index and also ranks at the bottom in the fundamental components, economic participation and opportunity and educational achievement. These results are a result of the Taliban's increasing rule over Afghanistan in every aspect of society, especially education and the economy, which has resulted in the disenfranchisement of women in the country. The rules set affect the number of women participating in education and the economy. Afghanistan, which always ranks at the bottom, even the index obtained in gender equality always decreases, illustrates that the objectives of the Global Gender Gap Index Report are not achieved in the country. In this study, to provide more specific accuracy to the results, the authors used qualitative research methodology through explanatory means. Data collection was conducted through primary and secondary sources. Primary sources are obtained from reports downloaded from the official WEF website and secondary data are obtained through books, journals, news, and data listed on various related official websites. The author uses a constructivist perspective with an international system level of analysis. The author analyzes the research results using Barnett and Finnemore's theory of international organizational dysfunction to explain the reasons for the failure to achieve WEF's goals in the Global Gender Gap Index Report in Afghanistan. The results showed that WEF's dysfunction in the Global Gender Gap Index Report in Afghanistan occurred due to material factors and cultural factors. In material factors, dysfunction occurs because of WEF's weak bureaucracy and Afghanistan has stronger power than WEF. In cultural factors, dysfunction occurs due to the weakness of activities carried out by WEF in achieving gender equality in the country and differences in values and culture between WEF and Afghanistan. Keyword: Taliban, Gender Equality, World Economic Forum, Global Gender GapIndexRepor